Mreža sestavin sodniškega poklica - Florjančič, Damijan (Pravnik, 2017)
In the article, the author critically discusses the procedure of qualification to became a judge in Slovenia. He states that from the starting point of this procedure (including the preparation for the state law exam), qualification is not suitable to the characteristics and requirements of judicial profession. On this basis he proposes its reformation. The author exposes the importance of judge's capability of self-control - when he is publicly exposed - especially when he comments judicial decisions. It may happen that judicial decisions are incorrect, erroneous or unlawful and are therefore often publicly commented. The author explains his view on when it is necessary to express apology to the affected persons in such cases.
Keywords: apology; judicial errors; opravičilo; pravniški državni izpit; qualification for judicial profession; samoomejevanje v javnosti; self-control in public; sodišča; sodstvo; state law exam; usposabljanje za sodniški poklic; zmotne sodne odločitve